Terapi Akupresur untuk Menangani Mual dan Muntah pada Pasien Kanker : Literature Review - Wahyudi Mulyaningrat; Ana Triana Wulandari (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Introduction. Cancer is the most common cause of death in the world. One treatment that is often used is chemotherapy. Chemotherapy has side effects such as nausea and vomiting. To reduce the side effects of nausea and vomiting in post-chemotherapy patients, complementary acupressure treatment P6 and St36 can be given which can improve the energy flow in the stomach so that it can overcome the symptoms of nausea and vomiting.Objective. The purpose of this literature review for doing a review of several literatures about acupressure therapy for cancer patients with chemotherapy who experience nausea and vomiting, so we will know the benefits of acupressure therapy.Methods. Article searches conducted electronically in some databases: Google Scholar , Portal Garuda and Proquest by 2014 until 2019. Keywords used were “acupressure”, “nausea vomit”, and “chemotherapy”, and finally got five articles matched. All five articles were selected using the PICO ( Patient, Intervention, Comparison, Outcome) method.Results. Acupressure intervention at point P6 and ST36 can reduce nausea and vomiting in post chemotherapy patients.Discussion. The use of acupressure method at point P6 and ST36 is effective in reducing nausea and vomiting in post chemotherapy patients. Acupressure therapy at point P6 and ST36 can be implemented and promoted in the treatment of nausea and vomiting in patients post chemotherapy.Conclusion. Stimulus at point P6 and ST36 can reduce nausea and vomiting in patients after chemotherapy.